Building a Literate Generation with a Bawean Touch: The Development of a Children’s Storybook for the School Literacy Movement (SLM) - Endang Setyowati; Ari Nugrahani; Kingkin Puput Kinanti (UIBU, 2025)
The main focus of this research is to develop a children's storybook based on the rich cultural heritage of the Bawean ethnic group, with a secondary aim of supporting and accelerating the School Literacy Movement (GLS) at the elementary school level. The specific target of this study is to develop, test the validity, and examine the practicality of a storybook grounded in Baweanese cultural heritage. The outcome of the storybook development can serve as a reference or supplementary reading material to help build a literate generation on Bawean Island. This study employs the Research and Development (R&D) method using the Borg and Gall model. This model was chosen due to its detailed development stages and its focus on the readability of the developed instructional material. However, due to time and resource limitations, the researcher was unable to implement the full Borg and Gall procedure. Product trials were conducted at a small and large scale in two elementary schools on Bawean Island. The validation process involved a series of assessments, including content evaluation by teachers, practicality assessments, and user responses from students. Data collected from surveys during the development phase were used as the basis for product revisions. The feasibility of the learning material was assessed by practitioners, language experts, media experts, and content experts. Validated aspects included: (a) content, (b) grammar, (c) illustrations, and (d) organization. The results yielded scores ranging from 85–100%, indicating the product is feasible and can be used to enhance GLS.